Said Ahmad's Uq Trilogy - An Artistic Representation Of The People's Spirit (Eurasian Journal of Humanities and Social Sciences, 2025)
In this article, Said Ahmad’s “Ufq” trilogy (“Qirq besh kun”, “Hijron kunlari”, and “Ufq”) is analyzed as one of the finest examples of realistic epic thinking in Uzbek literature. The trilogy, with its deep ideological and artistic content, depicts three major stages of the people's life — the years of labor before the war, the period of separation during the war, and the post-war reconstruction era —in a broad epic panorama. Through these works, the author masterfully conveys the spiritual values of human life such as patience, conscience, labor, love, national spirit, and hope